Morcegos Phyllostomidae (Mammalia, Chiroptera) em um mosaico agrícola no sudeste do Brasil: sazonalidade e frugivoria - Laurindo, Rafael de Souza (2015)
The conversion of forests into agricultural land has been occurring on an increasingly faster pace worldwide, especially in the tropical region. Thus, it is very important to study the abundance, composition and the factors that influence the dynamics of animal and plant community in these environments. The abundance and species richness in a particular location may be influenced by factors such as climatic conditions, interactions with competitors and predators, and availability of resources. This resource availability changes over time, resulting in shortages in food abundance, which contributes strongly to animal community dynamics in tropical environments, and influence the activity and composition of dietary patterns. The aim of this study was to investigate the abundance and diet of frugivores bats in an agricultural mosaic in southeastern Brazil, testing the hypothesis that the local structure of frugivores bat assemblage changes over time in response to availability of food resources. Sampling of bats was carried between December 2013 and January 2015, in a total of 70 nights, using ten mist nets. From February 2014 to January 2015, we followed the phenology of forest species whose fruits are consumed by bats. From December 2013 to October 2014, we collected fecal samples for diet identification. As expected, we detected a greater abundance and species richness in the hot rainy season, a period where the availability of resources was also higher. The results showed a positive relationship (r2 = 0.70) between fruit abundance and abundance of bats.